A ten year study of seed and litter production of different tree species of the broadleaved evergreen forests of the Coastal Cordillera of Valdivia - Donoso, Claudio; Hernández, Marcelo; Navarro, Celso (Bosque (Valdivia), 1993)
Data of 10 years of seed and litter production in evergreen forests of the Coastal Mountains of Valdivia with and without application of silvicultural treatments are analized. Data were collected monthly from 0,1 m2 boxes randomly placed on each of 1 hectare plots in three test plots, tree plots submitted to clear-cut, three plots under seed-tree treatment and two plots under shelterwood treatment. Monthly and seasonal tendencies of seed production and viability are determined for Laurelia philippiana, Saxegothaea conspicua, Amomyrtus luma, A. meli, Eucryphia cordifolia, Aextoxicon punctatum, Podocarpus nubigena, Gevuina avellana and Drimys winteri. Average litter production and monthly variation is also determined. Finally annual variation of seed production in ten years for all the species is analized. Only Aextoxicon punctatum shows a definite periodicity. The other species, require more years of study to clarify their tendencies.